pH-dependent hydrogels obtained by low molecular weight derivatives of aspartic acid and glutamic acid (L-Asp and L-Glu) - Daniela Tsekova; Vasilena Kondova; Konstantin Dochev; Borislav Anchev (Current Research in Biotechnology)
We report here the synthesis of two new anionic gemini surfactants, derivatives of L-Asp and L-Glu with analogous structure and their applications as low molecular weight gelators. Conditions for formation of pH-dependent hydrogels and their stability are presented and discussed. Although both compounds possess very close molecular structures, only one of them – the derivative of L-Asp, can form stable hydrogels. Loading of such a hydrogel with silver nanoparticles and the conditions of their release are also studied and described. Different methods to analyze molecular and supramolecular structures, such as NMR, FTIR, UV–VIS and SEM, are used to characterize the compounds and also to understand and follow the processes of loading and release of silver nanoparticles. It was found that a stable hydrogel can be formed only in acidic solution, while release can happen only at basic condition – over pH ≥ 9. The results obtained show that such pH-dependent hydrogels can be used for slowly and gradually supply of active compounds at necessity, expressed through changing the pH of the living tissue.